Batman : bad blood [videorecording (DVD)] - DeMatteis, J. M. (Warner Home Video, 2016)
During their investigation into Bruce Wayne's disappearance, even Alfred goes undercover to assist, and soon they all become involved with the mysterious Batwoman, who may have been the last to see Batman alive. As the Bat family continues to track him down, they come to the inescapable conclusion that the Dark Knight has gone over to the dark side, becoming Gotham's newest and most deadly crime boss.